Autonomous Curriculum Construction in Schools of San Juan de la Costa. (Revista LIDER, 2018)
This study describes preliminary results of research that aims to build an autonomous curriculum for the municipality of San Juan de la Costa. The educational proposal is developed in a participatory manner and the emphasis will be on the educational needs of the commune. Along with a tour of the reality of all schools in the district, a trawün with traditional authorities, the educational community and representatives of institutions (provincial and regional) was developed, to discuss the cultural, social and political bases the education in the territory should have.